2017
DOI: 10.1097/mpa.0000000000000847
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Markers (CD63 and CD9) Expression Pattern Using Immunohistochemistry in Resected Malignant and Nonmalignant Pancreatic Specimens

Abstract: Objectives Exosomes are important mediators in intercellular communications and play a role in cancer progression and metastasis. Exosomal membranes are enriched in endosome-specific tetraspanins (CD9 and CD63). Here, we explored the expression of CD63 and CD9 utilizing immunohistochemistry in malignant and non-malignant cells in 29 resected pancreatic specimens (RPS) of mixed racial background. Methods The pathologic tissues (PTs) and adjacent normal tissues (ANTs) in each RPS were stained for CD63 and CD9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 33 publications
(31 reference statements)
2
70
0
Order By: Relevance
“…Membranes of exosomes are enriched with numerous types of proteins, including cluster of differentiation (CD)63, CD9, CD37, CD53 and CD81 (19)(20)(21)(22); CD63 and CD9 are considered to be specific markers for exosomes (20). In the present study, CD63 was probed in order to determine whether exosomes has been successfully extracted from 293 cells (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Membranes of exosomes are enriched with numerous types of proteins, including cluster of differentiation (CD)63, CD9, CD37, CD53 and CD81 (19)(20)(21)(22); CD63 and CD9 are considered to be specific markers for exosomes (20). In the present study, CD63 was probed in order to determine whether exosomes has been successfully extracted from 293 cells (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We found that both exosome groups have exosome markers such as CD9 but TSG101 was only found in B7-H3 OE exosomes. CD9 is a tetraspanin, widely considered an exosome marker in various cell types including cancer cells [ 5 , 27 , 28 , 29 ]. TSG101 is an important component of the ESCRT-0 complex that promotes exosome secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The endosome specific tetraspanin CD63 is significantly enriched in exosomes and used as an established, classical biomarker for their immuno-affinity capture. Immuno-affinity capture is reported to yield high-quality exosomes [23,24,25]. Therefore, exosomes were further purified following the manufacturer's protocol using the CD63 antibody conjugated with magnetic beads (Invitrogen by Thermo Fisher Scientific Exosome-Human CD63 Isolation/Detection, Invitrogen #-10606D).…”
Section: Exosome Isolation and Purificationmentioning
confidence: 99%